CARDIOVASCULAR HEALTH AND DEMENTIA INCIDENCE AMONG OLDER ADULTS IN LATIN AMERICA: RESULTS FROM THE 10/66 STUDY. (16th November 2018) - Vidoni, M; Perales, J; Rodriguez, J; Vidoni, E; Burns, J; Guerchet, M; Lee, M
Abstract: A growing body of evidence shows that cardiovascular health is associated with brain health. Little is known about this topic among older adults in Latin America, where the incidence of dementia is rising. This study aimed to assess the longitudinal association between cardiovascular health and dementia in six Latin American countries. We analyzed longitudinal data from the 10/66 study and included non-demented residents at baseline aged 65 and older in Cuba, Dominican Republic, Peru, Venezuela, Mexico and Puerto Rico (n=6447) who were followed-up three years later on average. A modified Life's Simple 7 index of cardiovascular health (CVH; ranging from 0 to 14) was calculated based on scores in 7 modifiable health domains: exercise, diet, smoking, waist circumference, blood pressure, fasting glucose, and fasting cholesterol. The outcome was incident dementia, which was modeled using competing risks survival analysis to adjust for risk of death. Individuals with moderate or ideal levels of CVH had 37%-52% lower dementia risk than those with poor levels. Associations were most apparent among those in the lower 50% of wealth. Moderate and ideal levels of CVH in older ages may protect against dementia.